Molecular ion formation by photoinduced electron transfer at the tetracyanoquinodimethane/Au(111) interface - Gerbert, David; Tegeder, Petra (The journal of physical chemistry letters, 2017)
Optically induced processes in organic materials are essential for light harvesting, switching, and sensor technologies. Here we studied the electronic properties of the tetracyanoquinodimethane(TCNQ)/Au(111) interface by using two-photon photoemission spectroscopy. For this interface we demonstrated the lack of charge-transfer interactions, but we found a significant increase in the sample work function due to UV-light illumination, while the electronic structure of the TCNQ-derived states remain unaffected. Thereby the work function of the interface can be tuned over a wide range via the photon dose. We assigned this to a photoinduced metal-to-molecule electron transfer creating negative ions. The electrons are bound by a small potential barrier. Thus thermal activation reverses the process resulting in the original work function value. The presented photoinduced charge transfer at the TCNQ/Au(111) interface can be used for continuous work function tuning across the substrate’s work function, which can be applied in device-adapted hole-injection layers or organic UV-light sensors.